2019
DOI: 10.1158/1538-7445.am2019-2568
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2568: Investigation of Fanconi Anemia pathway downstream genes

Abstract: Introduction: A key response mechanism to DNA damage is the Fanconi Anemia repair pathway (FA), which involves homologous recombination DNA repair and is activated through mono- ubiquitination of FANCD2. FA deficiency is considered to increase the sensitivity of tumors to particular DNA-targeted agents, and may prove to be a target of cancer treatment. We hypothesize that FA deficient tumors have a low growth rate and reduced ability for DNA repair compared to FA functioning tumors. Given that genetic modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…FANCC regulates nuclear translocation of β-catenin and works as a transcriptional repressor of β-catenin downstream gene DKK1 [102]. Besides these case studies, An RNA-seq study revealed a collection of genes with altered expression among which a large portion are implicated in oncogenic processes [103]. Further studies are needed to explore the potential transcriptional regulation role of FA proteins especially in cancer contexts where FA gene expression is found to be high.…”
Section: Transcriptional Regulation Functions Of Fa Proteinsmentioning
confidence: 99%
“…FANCC regulates nuclear translocation of β-catenin and works as a transcriptional repressor of β-catenin downstream gene DKK1 [102]. Besides these case studies, An RNA-seq study revealed a collection of genes with altered expression among which a large portion are implicated in oncogenic processes [103]. Further studies are needed to explore the potential transcriptional regulation role of FA proteins especially in cancer contexts where FA gene expression is found to be high.…”
Section: Transcriptional Regulation Functions Of Fa Proteinsmentioning
confidence: 99%